Evaluasi Kesesuaian Lahan Pertanian Pasca Lebih dari 10 Tahun Erupsi Gunung Sinabung Kabupaten Karo Sumatera Utara - Nani Kitti Sihaloho; Susilo Budiyanto; Anasrullah Anasrullah; Chaieydha Noer Afiefah (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2026)
Karo Regency, North Sumatra, is widely recognized as a major agricultural production center in Indonesia, particularly for vegetables, fruits, and ornamental crops, where the primary livelihoods of the population depend on food crops, horticulture, and mixed plantations. The region is also home to Mount Sinabung, an active volcano that re-erupted on August 27, 2010, after a long period of dormancy. More than ten years after the eruption, volcanic deposits have undergone gradual weathering processes that contribute to soil development. Through physical, chemical, and biological weathering, volcanic materials release essential nutrients that can enhance soil fertility and support agricultural production. However, comprehensive studies evaluating agricultural land suitability more than ten years (>10 years) after the eruption, based on current soil physical and chemical conditions, remain limited, particularly in identifying both actual and potential limiting factors affecting land utilization. This study aims to assess agricultural land suitability more than ten years after the eruption of Mount Sinabung in Karo Regency, North Sumatra. The evaluation was conducted to identify land potential and limiting factors that continue to influence post-eruption agricultural land use. The research employed a survey method using the FAO land suitability evaluation framework. The analyzed data included climatic conditions, soil physical and chemical properties, and land characteristics relevant to crop growth. Soil samples were collected at depths of 0–30 cm and 30–60 cm from eight villages representing variations in distance from the volcano and levels of volcanic material exposure. The urgency of this research lies in evaluating the current suitability level and carrying capacity of agricultural land more than a decade after the eruption to ensure appropriate commodity selection and management strategies based on present bio-physical conditions. The results indicate that agricultural land in the study area has undergone considerable recovery, although it still exhibits characteristics of young volcanic soils with dynamic properties. Land suitability evaluation shows that potato and Arabica coffee demonstrate relatively better adaptation, with actual and potential suitability classes ranging from S1 to S2 after improvements in dynamic limiting factors such as nutrient retention, rooting media, and water availability. In contrast, avocado development remains relatively limited due to temperature constraints, which are inherent and difficult to modify. These findings emphasize that land suitability evaluation is essential as a scientific basis for determining appropriate commodities and sustainable land management strategies in post-volcanic eruption areas.